Analysis of the pretreatment process of gonggong shell flour (Laevistrombus turturella) on a scale up - Diyah Dewanti, Beauty Suestining; Rumandhani, Nuvia Nurlaily; Febrianto, Arie; Widayanti, Vindhya Tri; Rucitra, Andan Linggar; Rohmah, Wendra Gandhatyasri; Septifani, Riska; Ikasari, Dhita Morita (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The gonggong shell (Laevistrombus turturella) is a species of sea snail found in the waters surrounding Bintan, Riau Islands. The gonggong consists of both meat and shell, with the shell constituting the largest portion, approximately 60%. The high proportion of shells materials compared to  the meat results in abundant gonggong shell waste. One way to utilize gonggong shells is by converting the shells into shell flour, which can be used in health supplements and as feed for shrimp, particularly in shrimp farms in Bintan Regency. The hard texture of gonggong shells (13.1 MPa) requires pretreatment before milling. The pretreatment processes include autoclaving, drying, and burning. This study aimed to assess the quality difference between the scaled-up  and laboratory-scale processes, and to identify the material requirements and utilities for the large-scale pretreatment process of gonggong shell to produce shell flour. The scale-up was conducted with a 1 : 50 ratio from the laboratory scale. The quality results of gonggong shell flour in the large-scale study showed a moisture content of 0.46%, an ash content of 56.42%, and a calcium content of 54.31%. These results were compared with those obtained at the laboratory scale using an unpaired t-test, and no significant differences were found for all tested parameters.